Escalation of commitment in entrepreneurship-minded groups. Issue 4 (27th May 2014) - G. Markovitch, Dmitri; Huang, Dongling; Peters, Lois; Phani, B.V.; Philip, Deepu; Tracy, William
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate commitment escalation tendencies and magnitude in groups of entrepreneurship-minded decision makers. Design/methodology/approach – The paper uses a software-based management simulation to expose 447 graduate business students in the USA and India to research stimuli under conditions that resemble important aspects of entrepreneurs' business environment, such as a focus on overall firm performance. Unlike most previous escalation research that studied individuals, the primary unit of analysis is a three-person group. Findings – The paper demonstrates a positive relationship between the groups' entrepreneurial intentions and escalation magnitude. The paper also finds a direct relationship between sunk costs and subsequent investment amounts, suggesting an additional route through which sunk costs may impact escalation behavior – anchoring and insufficient adjustment. Practical implications – The authors hope that the findings will stimulate further research on commitment escalation modalities and mechanisms among entrepreneurship-minded decision makers and provide impetus for efforts to develop effective debiasing strategies. Originality/value – The study addresses a long-standing gap in entrepreneurship research, by demonstrating a significant positive relationship between entrepreneurial intentions and escalation behaviors. Also noteworthy, the results are generated using a different research method (simulation) than the experimental approach used in most extant escalation research. As such, the exploration provides important triangulating evidence that is currently lacking from the rich escalation literature.